The Development of ROV (Remotely Operated Vehicle) by Applying PID (Proportional Integral Derivative) for Monitoring and Preservation of Coral Reefs at Pasir Putih Beach Situbondo - Budianto; Sutrisno, Imam; Widiarti, Yuning; Rahmat, Mohommad Basuki (Bulletin of Community Engagement, 2024)
The necessity for the monitoring of coral reefs is becoming increasingly apparent, in order to facilitate the tracking of the health and development of these ecosystems. It is for this reason that underwater operating robots (ROVs) are being employed as an effective tool for the monitoring of coral reefs. ROVs are capable of diving to varying depths, accessing difficult-to-reach locations, and providing comprehensive visualisation through cameras and sensors. They are also equipped with an ROV depth system that, upon reaching a specified depth, enables the ROV to manoeuvre according to the user's instructions and to support its movements using the PID (Proportional Integral Derivative) Method. This research will investigate the potential of various ROV technologies for optimising the monitoring of coral reefs, including mapping, sampling, and environmental parameter measurement capabilities. The ability of ROVs to collect data in real-time without disturbing the ecosystem provides an advantage in long-term monitoring of changes in coral reefs. Furthermore, the potential challenges associated with the utilisation of ROVs for coral reef monitoring, including operational costs, technical maintenance, and the integration of complex data, are also addressed. Potential solutions to these challenges are also presented in order to facilitate the development and application of ROVs in coral reef monitoring. The combination of the advanced technology of ROVs with the urgent need for coral reef monitoring will facilitate a more comprehensive understanding of the health of these ecosystems, thereby enabling the implementation of proactive measures for the conservation and protection of coral reefs worldwide.